Analysis of capecitabine plus oxaliplatin (xelox) combination in the management of metastatic colorectal cancer compare with fluorouracil and oxaliplatin combination (folfox) - Miladiyah, Isnatin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : Combinations of Fluorouracil (FU) and biomodulator Leucovorin (LV) established as a standard regimen for therapy of colorectal cancer with metastases. To give better antitumor activity in colorectal cancer therapy, oxaliplatin is combined with FU/LV and give significant improvement. Fluorouracil can only be given by intravenous administration. This limitation raised effort to find alternative drugs that can be given orally, such as capecitabine. Capecitabine is an oral FU prodrug, with high oral bioavailability, highly accumulated in neoplastic tissue to be converted in FU, and well tolerated. Some clinical studies revealed effectivity of capecitabine plus oxaliplatin (XELOX) compared to FU/LV plus oxaliplatin (FOLFOX). Objective : This article is aimed to compare non inferiority of XELOX to FOLFOX in colorectal cancer with metastases, viewed form primary outcomes and secondary outcomes. Results : XELOX was comparable to FOLFOX with some benefitsover FOLFOX. Conclusion : XELOX could be considered as FOLFOX replacement as a standard therapyfor colorectal cancer with metastases.